In Vitro/In Vivo Correlation of Two Extended-Release Cilostazol Formulations - Min, Kyoung Ah; Kim, Na Young; Jin, Min Jeong; Kim, Doyeon; Ma, Yoonseo; Karna, Sandeep; Park, Young Joon (Pharmaceuticals, 2024)
This study aims to evaluate and determine the correlation between in vitro release and in vivo pharmacokinetics of two extended-release dosage forms of Cilostazol. In vitro release profiles for two dosage forms, tablet and capsule, were analyzed under physiologically mimicked medium conditions using the paddle and basket USP release apparatus. A single-dose, two-period crossover study design in beagle dogs was applied for the pharmacokinetic study. The fed and fast effects were considered for evaluation. Pseudo gastric release medium transfer setup study from pH 1.2 to pH 6.8 (+0.5% SLS) and pH 1.2 to pH 6.8 (+1.0% SLS) demonstrated that Pletaal® SR 200 mg capsules have higher drug release rates than Cilostan® CR 200 mg tablets. Similarly, in vivo study showed Cilostazol concentration in plasma and AUC was lower under the fast state than the fed state. The ratio of least squared geometric mean values, Cmax, AUC0-t, and AUC0-inf of Cilostazol were 2.53-fold, 2.89-fold, and 2.87-fold higher for Pletaal® SR 200 mg capsules compared with Cilostan® CR 200 mg tablets, respectively. Correlation of in vitro/in vivo data indicated that Pletal® SR 200 mg capsules have better release and pharmacodynamic effect than Cilostan® CR 200 mg tablets.
Keywords: capsule; cilostazol; in vitro; in vivo; pharmacokinetics; release; two-period crossover design